Genome-wide analysis of the U-box E3 ubiquitin ligase family role in drought tolerance in sesame (Sesamum indicum L.) - Cao, Hengchun; Tian, Qiuzhen; Ju, Ming; Duan, Yinghui; Li, Guiting; Ma, Qin; Zhang, Haiyang; Zhang, Xianmei; Miao, Hongmei (Frontiers in Plant Science, 2023)
Plant U-box (PUB) proteins belong to a class of ubiquitin ligases essential in various biological processes. Sesame (Sesamum indicum L.) is an important and worldwide cultivated oilseed crop. However few studies have been conducted to explore the role of PUBs in drought tolerance in sesame. This study identified a total of 56 members of the sesame PUB family (SiPUB) genes distributed unevenly across all 13 chromosomes. Based on phylogenetic analysis, all 56 SiPUB genes were classified into six groups with various structures and motifs. Cis-acting element analysis suggested that the SiPUB genes are involved in response to various stresses including drought. Based on RNA-seq analysis and quantitative real-time PCR, we identified nine SiPUB genes with significantly different expression profiles under drought stress. The expression patterns of six SiPUB genes in root, leaf and stem tissues corroborated the reliability of the RNA-seq datasets. These findings underscore the importance of SiPUB genes in enhancing drought tolerance in sesame plants. Our study provides novel insights into the evolutionary patterns and variations of PUB genes in sesame and lays the foundation for comprehending the functional characteristics of SiPUB genes under drought-induced stress conditions.